2022
DOI: 10.1371/journal.pone.0265956
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of boron seed priming on seedling establishment, growth, and grain biofortification of mungbean (Vigna radiata L.) in yermosols

Abstract: Boron-deficiency in Yermosols is among the major constraints to mungbean productivity and grain biofortification in Pakistan. However, agronomic strategies such as boron (B) seed priming have potential to improve mungbean yield and grain biofortification. Moreover, deficiency to toxicity range for B is very narrow; therefore, it is pre-requisite to optimize its dose before field evaluation. A wire house experiment was planned out to reconnoiter the impact of seed priming with B on growth and quality of two cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Among the different landraces of sweet corn, late emergence (8.6 days) was noted in the Kunarh landrace, which followed Mingora (8.4 days), while early emergence (7.8 days) was recorded in the Kashmir landrace of sweet corn. The results of the current investigation are in accordance with the reports of Rehman et al, (2022) who reported that primed seed decreased the emergence time and improved germination compared to dry seed or control. The results also follow those of Irshad et al (2022) & Mashamaite et al (2022, who established that Moringa leaf extract encouraged earlier emergence and seedling growth.…”
Section: Days To Emergencesupporting
confidence: 92%
“…Among the different landraces of sweet corn, late emergence (8.6 days) was noted in the Kunarh landrace, which followed Mingora (8.4 days), while early emergence (7.8 days) was recorded in the Kashmir landrace of sweet corn. The results of the current investigation are in accordance with the reports of Rehman et al, (2022) who reported that primed seed decreased the emergence time and improved germination compared to dry seed or control. The results also follow those of Irshad et al (2022) & Mashamaite et al (2022, who established that Moringa leaf extract encouraged earlier emergence and seedling growth.…”
Section: Days To Emergencesupporting
confidence: 92%
“…The response pattern showed that borax application at a dose of 7.2 mg B kg -1 increased the vegetated area and DMY in comparison with the control treatment. This positive effect on seed emergence and seedling development was also shown by Rehman et al (2022). However, with borax application above 7.2 mg B kg -1 , increasing doses decreased the vegetated area and DMY as a result of B toxicity, resulting in the complete absence of germination at a dose of 115.2 mg B kg -1 .…”
Section: Seedling Toxicity Trialmentioning
confidence: 64%
“…Priming solutions commonly used are hydropriming (using water), 23 osmopriming (involving polyethylene glycol and inorganic salts), 24 hormonal priming, 25 and nutrient priming. 26 However, the effectiveness of these priming solutions can vary depending on the properties of the solution and the specific requirements of different crop species. 27 Integrating ENMs into seed priming processes offers a novel approach to enhance crop productivity and quality potential, providing valuable solutions for sustainable agriculture.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This technique initiates metabolic activities associated with germination without the emergence of the radicle. Priming solutions commonly used are hydropriming (using water), osmopriming (involving polyethylene glycol and inorganic salts), hormonal priming, and nutrient priming . However, the effectiveness of these priming solutions can vary depending on the properties of the solution and the specific requirements of different crop species .…”
Section: Introductionmentioning
confidence: 99%